Verb Denoting the Concept of "Eating" (English Versus Vietnamese) - Trương Thị Huệ (2005)
The thesis is designed to investigate verbs denoting the concept of "eating" in English and Vietnamese in cognitive semantic perspective. The research aims to identify the similarities and differences in the ways of using these verbs, from that it shows that the difference in cultural leads to the difference in using language, it also gives the implication in teaching and learning foreign languages in general and English in particular.